2003
DOI: 10.1002/elan.200302815
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effects on the Selectivity of Mercuracarborand Ionophores in Ion‐Selective Electrodes and Membrane Formulations for Their Use in High Protein Concentration Environments

Abstract: Ion-selective electrodes based on the ionophore [9]mercuracarborand-3 (MC3) have been demonstrated in the past to be highly selective for the chloride ion. This ionophore is macrocyclic and possesses Lewis acidic mercury centers, both of which result in enhanced ionophore binding to spherical anions. Like their charge-reverse analogs, crown ethers, mercuracarborands offer the possibility to tune binding selectivity through changes in cavity size and/or via the incorporation of functional groups onto the cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…An equally efficient optode has been built by using 4′,5′-dibromofluorescein octadecyl ester as the revealing proton chromoionophore . Successively, it was found by the same authors that the addition of two peripheral methyl groups to each carborane of the macrocycle (Figure ) resulted in a less selective ion carrier, because of the weakening of the Lewis acidity of the mercury centers due to the presence of electron-donating methyl groups …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An equally efficient optode has been built by using 4′,5′-dibromofluorescein octadecyl ester as the revealing proton chromoionophore . Successively, it was found by the same authors that the addition of two peripheral methyl groups to each carborane of the macrocycle (Figure ) resulted in a less selective ion carrier, because of the weakening of the Lewis acidity of the mercury centers due to the presence of electron-donating methyl groups …”
Section: Applicationsmentioning
confidence: 99%
“…229 Successively, it was found by the same authors 229 that the addition of two peripheral methyl groups to each carborane of the macrocycle (Figure 76) resulted in a less selective ion carrier, because of the weakening of the Lewis acidity of the mercury centers due to the presence of electron-donating methyl groups. 230 With the exception of this noteworthy study, anionic boron clusters have been much more frequently tested as ion exchangers than as ion carriers. Bakker et al 231 Interestingly, both showed a marked selectivity improvement over Cd 2+ .…”
Section: Redox-driven Applications Of Boron-cluster-based Materialsmentioning
confidence: 99%
“…The icosahedral carboranes, closo -1,2-C 2 B 10 H 12 ( o -carborane), closo -1,7-C 2 B 10 H 12 ( m -carborane), and closo -1,12-C 2 B 10 H 12 ( p -carborane), have been the subject of investigation in areas as diverse as host−guest chemistry, catalysis, ion sensing, and materials science as well as medicinal chemistry applications . Key to this variety of applications is the unique properties of carboranes, such as resistance to catabolism, kinetic inertness to reagents, rigidity, and strong hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cyclic ionophores with a geometrically preorganized central cavity is well-established in cation-selective electrodes. Many of these ionophores interact with spherical cations that fit best within the macromolecular cavity and result in electrodes that have very good selectivity to their primary cations. Wide-spread use of cyclic ionophores has not met with similar success in the case of anion-selective electrodes. Indeed, there is a limited number of reports describing successful anion-selective cyclic ionophores. A cyclic mercuracarborand ionophore with a well-defined Lewis acidic central cavity has been introduced. , The ionophore was used for the selective determination of chloride in biological samples. Later on, with careful control of the ion fluxes across the membrane, nanomolar iodide detection using the same mercuracarborand has been achieved .…”
mentioning
confidence: 99%
“…[19][20][21][22] Indeed, there is a limited number of reports describing successful anion-selective cyclic ionophores. [23][24][25] A cyclic mercuracarborand ionophore with a well-defined Lewis acidic central cavity has been introduced. 23,24 The ionophore was used for the selective determination of chloride in biological samples.…”
mentioning
confidence: 99%